Gods and Goddesses in the Garden : Greco-Roman Mythology and the Scientific Names of Plants - Bernhardt, Peter, 1952- (Book collections on Project MUSE., 2008)
"In Gods and Goddesses in the Garden, botanist Peter Bernhardt reveals the rich history and mythology that underlie the origins of many scientific plant names. Unlike other books about botanical taxonomy that take the form of heavy and intimidating lexicons, Bernhardt's account comes together in a series of interlocking stories. Each chapter opens with a short version of a classical myth, then links the tale to plant names, showing how each plant "resembles" its mythological counterpart with regard to its history, anatomy, life cycle, and conservation. You will learn, for example, that as our garden acanthus wears nasty spines along its leaf margins, it is named for the nymph who scratched the face of Apollo. The shape-shifting god, Proteus, gives his name to a whole family of shrubs and trees that produce colorful flowering branches in an astonishing number of sizes and shapes." "Amateur and professional gardeners, high school teachers and professors of biology, botanists and conservationists alike will appreciate this book's entertaining and informative entry to the otherwise daunting field of botanical names. Engaging, witty, and memorable, Gods and Goddesses in the Garden transcends the genre of natural history and makes taxonomy a topic equally at home in the classroom and at cocktail parties."--Jacket